(untitled) (Journal of Hama University, 2020)
The aim of this prospective clinical study is to evaluate the efficacy of application d-PTFE in fresh alveolar socket - Post Extraction on the absorption of the alveolar bone after extraction. In this study, 40 single root teeth were extracted in 35 patients (24 females and 11 males) from the mandible. d-PTFE applied over the fresh alveolar sockets of (20) teeth (group 1) The remaining 20 teeth (group II) were left to heal spontaneously. Measurements were performed at three periods (immediately after extraction, after three months, and after six months of extraction) using the Ez-3D Plus program on the Cross-Section of the alveolar ridge of the CTBT. The measurements were performed in the center of alveolus of the extracted teeth with the aim of studying the changes in height of the alveolar margin: the measurements were taken from the top of the alveolar ridge to the lower edge of the mandible. The results of this study showed statistically significant differences between the averages of the height changes of the alveolar (P >0.05) for all comparisons after (three and six months), the average of height reduction in d-PTFE group was 1.31±0.23 mm and 2.89±0.49 mm in control group while the average of height reduction in d-PTFE group after six months was 1.98±0.35 and 3.93±0.51 in control group. Conclusion : applying d-PTFE over fresh alveolar socket - Post Extraction reduces the absorption of alveolar ridge height. It’s recommended to apply d-PTFE over the alveolar socket post extraction in the context of alveolar ridge preservation